2022
DOI: 10.3390/ani12213059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anionic and Zeolite Supplements and Oral Calcium Bolus in Prepartum Diets on Feed Intake, Milk Yield and Milk Compositions, Plasma Ca Concentration, Blood Metabolites and the Prevalence of Some Reproductive Disorders in Fresh Dairy Cows

Abstract: Hypocalcaemia is an important disorder associated with an increased risk of metabolic diseases, and many studies have been going on for decades. This study investigated the effects of anionic and zeolite with an oral Ca bolus in the prepartum phase on milk yields and compositions, and plasma Ca concentrations, blood metabolites and the prevalence of some reproductive disorders in dairy cows after parturition. Ninety pregnant non-lactating Holstein-Friesian cows were randomly assigned to three isoenergetic diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Similar results were obtained by Maity et al. (2021) and Masoumi Pour et al. (2022) by lowering blood BHB levels after zeolite supplementation in dairy cow diets.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were obtained by Maity et al. (2021) and Masoumi Pour et al. (2022) by lowering blood BHB levels after zeolite supplementation in dairy cow diets.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, based on this study, it's suggested that increased glucose levels and the reduction in ketosis incidence have positive effects on uterine health. Although the detailed mechanism of zeolite's action on reproductive health isn't fully understood, there are apparent benefits in reducing uterine pathology ( Masoumi et al., 2022 ).Therefore, by numerically establishing the bacterial population for the two groups, it can be noted that for the T group the bacteria was present in a smaller number in the uterin secretions. A plausible explanation could indeed involve a more robust local immune response within the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Low calcium levels during this phase can lead to various complications such as hypocalcemia, displaced abomasum, ketosis, metritis, and placental retention. Ruminants rely on gluconeogenesis, a process crucial for maintaining energy levels, especially during the periparturient period (Masoumi Pour et al, 2022).…”
Section: Discussionmentioning
confidence: 99%